PERAN GURU DALAM MENINGKATKAN KREATIVITAS BELAJAR PESERTA DIDIK SMKS SETIA BUDI BINJAI 2024/2025 - Kurnia putri, Dita; Hamidah Darma; Maulana Akbar Sanjani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the role of teachers in enhancing student creativity in the learning process, the factors that support and hinder this role, and how teachers apply learning to encourage creativity in the learning process at SMKS Setia Budi Binjai. This study uses a qualitative descriptive method. The subjects of this study are teachers and students. Data collection techniques were carried out through observation and interviews. Data analysis techniques used the Miles and Huberman model, which consists of three stages, namely data reduction, data presentation, and conclusion formulation. The results of the study indicate that teachers at SMKS Setia Budi Binjai actively fulfill their roles by using various learning methods, creative tools, and providing space for students to explore. Supporting factors include adequate school facilities, a conducive classroom environment, and students' enthusiasm for learning. Inhibiting factors involve limited time, varying student abilities, and students’ lack of confidence. The learning implementation is active and participatory, encouraging students to think creatively through discussions, projects, and presentations.